Impact of nanosilver on gut microbiota: a vulnerable link. (March 2018) - Dahiya, Dinesh Kumar; Renuka,; Puniya, Anil Kumar
A plethora of nanoparticles are currently used in the food industry in myriad applications. Of these, 'nanosilver' is widely used due to their multitude actions. Recent consensus among the scientific community affirmed that nanosilver might potentially alter the gut microbiota instead of their intended use that has a profound effect on our health. Dysbiosis of gut microbiota led to the onset of serious pathological conditions as reflected from several studies. In lieu of the positive impact of nanosilver, their inadvertent toxic effects on gut microbiota are underestimated. In this review, first all studies concerning the influence of nanosilver on gut microbiota are discussed along with relevant pharmacokinetic studies and in closing section the challenges and future task remained in the field are highlighted.